Bioinformatics and expression analysis of the Xeroderma Pigmentosum complementation group C (XPC) of Trypanosoma evansi in Trypanosoma cruzi cells Análises de bioinformática e da expressão do gene Xeroderma Pigmentosum complementation group C (XPC) de Trypanosoma evansi em células de Trypanosoma cruzi - Souza K.M.* (2023)
© 2023, Instituto Internacional de Ecologia. All rights reserved.Nucleotide excision repair (NER) acts repairing damages in DNA, such as lesions caused by cisplatin. Xeroderma Pigmentosum complementation group C (XPC) protein is involved in recognition of global genome DNA damages during NER (GG-NER) and it has been studied in different organisms due to its importance in other cellular processes. In this work, we studied NER proteins in Trypanosoma cruzi and Trypanosoma evansi, parasites of humans and animals respectively. We performed three-dimensional models of XPC proteins from T. cruzi and T. evansi and observed few structural differences between these proteins. In our tests, insertion of XPC gene from T. evansi (TevXPC) in T. cruzi resulted in slower cell growth under normal conditions. After cisplatin treatment, T. cruzi overexpressing its own XPC gene (TcXPC) was able to recover cell division rates faster than T. cruzi expressing TevXPC gene. Based on these tests, it is suggested that TevXPC (being an exogenous protein in T. cruzi) interferes negatively in cellular processes where TcXPC (the endogenous protein) is involved. This probably occurred due interaction of TevXPC with some endogenous molecules or proteins from T.cruzi but incapacity of interaction with others. This reinforces the importance of correctly XPC functioning within the cell.